Visible-light driven water splitting over BiFeO3 photoanodes grown via the LPCVD reaction of [Bi(OtBu)3] and [Fe(OtBu)3]2 and enhanced with a surface nickel oxygen evolution catalyst. Issue 39 (18th September 2015) - Moniz, Savio J. A.; Blackman, Christopher S.; Southern, Paul; Weaver, Paul M.; Tang, Junwang; Carmalt, Claire J.
Abstract : LPCVD-grown BiFeO3 films show enhanced visible-light driven activity for PEC water splitting, which dramatically improves on addition of a surface nickel oxygen evolution catalyst. Abstract : Phase-pure BiFeO3 films were grown directly via dual-source low-pressure CVD (LPCVD) from the ligand-matched precursors [Bi(O t Bu)3 ] and [Fe(O t Bu)3 ]2, without the requirement for oxidising gas or post deposition annealing. Photocatalytic testing for water oxidation revealed extremely high activity for PEC water splitting and photocatalytic water oxidation under visible light irradiation ( λ > 420 nm) with a benchmark IPCE for BiFeO3 of 23% at 400 nm. The high activity is ascribed to the ultrafine morphology achieved via the LPCVD process. The performance was enhanced by over four times when the BiFeO3 photoanode is coupled to a Ni–B surface OEC.